Cenas do cotidiano e da sexualidade de pessoas idosas institucionalizadas - Razeira, Tatiane Rocha (2016)
The aging process produces transformations, changes and adaptations in people's lives in different ways, revealing a vast field and still unknown by its scope and complexity, arises the need to reveal their subjectivities in search of understanding and knowledge construction. Thus, this study aimed to understand how institutionalized elderly people experience daily life and their sexuality. The methodological approaches used were of ethnographic inspiration, which used observations and informal conversations, recorded in a field diary. In this research the daily life is characterized by live every day in which develop aspects of personality and for this use the senses, mental abilities, emotions, passions and ideologies. And sexuality that has a large size, it is historical, social, unfinished and allows new meanings, and perhaps also to set it as a stark silence. Research has shown that the great challenge that involves the themes is to provide older people express their sexuality without guilt, with possibilities and fluidity and institutionalizing itself as a possible alternative and even necessary to contemporary family configurations.